(untitled) (Research, Society and Development, 2021)
Hospital infections are a challenge for public health, given their impact on patient prognosis and hospital costs. The objective of this article was to evaluate the bacterial occurrence and the bacterial profile of tracheal aspirates of patients admitted to the ICU. Retrospective, descriptive and documentary study, having as source spreadsheets available by the Laboratory of Clinical Analysis of the University Hospital. Results Of the 307 reports analyzed in 2017, 142 were positive, and in 2018 out of 319, 213 were positive. The most frequent microorganism in the two years was Acinetobacter baumannii, followed by Pseudomonas aeruginosa, Staphylococcus aureus and Klebsiella pneumoniae. Acinetobacter baumannii showed resistance to several bethalactamics, including meropenem and imipenem and ampicillin sulbactam; sensitive to colistin and tigecycline. The isolates of P. aeruginosa from 2017 and 2018 were resistant to: meropenem, imipenem, ceftazidima, cefepima, ciprofloxacin and levofloxacin. However, for piperacillin tazobactam resistance was observed in the samples obtained in 2018. S. aureus was resistant to clindamycin, sulfamethoxazole trimethoprima and oxacillin; showed sensitivity to linezolid, tigeclicline and vancomycin. K. pneumoniae isolates showed resistance, among other drugs, to imipenem, meropenem, piperacillin tazobactam; on the other hand, amicacin and colistin were sensitive. The observed resistances denote the importance of the rational use of antimicrobials and provide data for the creation of empirical antibiotic therapy protocols for the treatment of patients hospitalized in the Institution.